Penyuluhan Kepada Mahasiswa Baru Tentang Menumbuhkan Ide Bisnis Untuk Membangun Rencana Sukses Dalam Industri Pariwisata - Ratnaningtyas, Heny; Aditya, Michael Khrisna (Jurnal Pemberdayaan Pariwisata; Vol 6 No 1 (2024): Jurnal Pemberdayaan PariwisataDO - 10.30647/jpp.v6i1.1814, 2024)
The aim of this outreach activity is to provide a deeper understanding of the essence and value of the Entrepreneurship Study Program, as well as provide inspiration and motivation to new students to consider careers and education in this field. The implementation method is carried out through online assistance using the Zoom platform which includes counseling, socialization and direct consultation. The material that will be presented includes important steps in creating a business idea, starting from assessing interests and skills, identifying problems or needs, developing creative solutions, to planning a business and starting a small-scale business. This socialization activity provides wider access for new students to gain an in-depth understanding of the practical steps in creating business ideas, as well as facilitating direct interaction between new students and experienced entrepreneurship practitioners to gain valuable insights and views. This counseling also aims to increase new students' motivation and interest in exploring entrepreneurial potential through interactive and in-depth learning, as well as expanding new students' networks and connections with the wider entrepreneurial community. This opens up potential collaboration and mentorship opportunities to support their future career and business development. Keywords: interactive counseling, business idea creation, motivation and interest